HPLC Determination of 5-Fluorouracil in Human Plasma - Krishnaiah, Y.S.R.; Satyanarayana, V.; Bhaskar, P.; Jayaram, B. (Asian Journal of Chemistry, 2010)
The present study describes the HPLC method for the estimation of 5-fluorouracil in human plasma Varying amounts of 5-fluorouracil (10 to 400 ng) were added to drug-free human plasma (0.5 mL) and mixed with 0.3 mL of acetonitrile. The mixture was vortexed for 5 min and centrifuged at 3,000 rpm for 10 min and the supernatant liquid was fIltered. Twenty microlitres of the resultant fIltrate was injected into a reverse phase C-18 column using a mobile phase consisting of HPLC grade water at a flow rate of 0.8 mL/min. The eluents were monitored at 260 nm. On conducting validation study, it was found that the method is simple, precise, specific, less time consuming and accurate for the estimation of 5-fluorouracil in human plasma samples.